Strategic structure–activity relationship study on a follistatin-derived myostatin inhibitory peptide. (15th August 2021) - Saitoh, Mariko; Takayama, Kentaro; Roppongi, Yoshimi; Shimada, Takahiro; Taguchi, Akihiro; Taniguchi, Atsuhiko; Hayashi, Yoshio
Graphical abstract: Abstract: Myostatin, a negative regulator of muscle mass is a promising target for the treatment of muscle atrophic diseases. The novel myostatin inhibitory peptide, DF-3 is derived from the N -terminal α-helical domain of follistatin, which is an endogenous inhibitor of myostatin and other TGF-β family members. It has been suggested that the optimization of hydrophobic residues is important to enhance the myostatin inhibition. This study describes a structure–activity relationship study focused on hydrophobic residues of DF-3 and designed to obtain a more potent peptide. A methionine residue in DF-3, which is susceptible to oxidation, was successfully converted to homophenylalanine in DF-100, and a new derivative DF-100, with four amino acid substitutions in DF-3 shows twice the potent inhibitory ability as DF-3. This report provides a new platform of a 14-mer peptide muscle enhancer.